Low-temperature fabrication of Pr-doped In2O3 electrospun nanofibers for flexible field-effect transistors. Issue 42 (13th October 2022) - Shi, Wei; Peng, Zefei; Chen, Song; Yan, Xueling; Xu, Hua; Liu, Lan
Abstract : High-quality Pr-doped In2 O3 (InPrO) nanofibers were fabricated by a combustion synthesis at a relatively low temperature (380 °C) and the InPrO based FET with high bending stability was successfully fabricated on the PI substrate. Abstract : Although metal oxide nanofibers (MO-NFs) based field-effect transistors (FETs) prepared by electrospinning have gained great attention, it is still challenging to develop MO-NFs directly on flexible substrates such as polyimide (PI) to achieve a high flexibility due to the high annealing temperature. In this work, using a UV pretreatment and a subsequent "combustion synthesis" process, high-quality Pr-doped In2 O3 (InPrO) electrospun NFs were successfully fabricated on a flexible PI substrate at a relatively low temperature (380 °C). It was found that the InPrO-based flexible FET (f-FET) prepared by UV pretreatment and low annealing temperature not only has a good interfacial adhesion but also show a good flexibility. When the f-FET was wrapped around the rigid cylindrical rod with a radius of 5 mm, it exhibited good performance including a high μ FE of 2.12  cm 2 V −1 s −1, a large I on / I off of ∼10 8, and an excellent cycling stability (1000 bending cycles). This low-temperature processing route will certainly contribute to the future flexible electronics manufacturing.